UPAYA PENINGKATAN KUALITAS KESEHATAN MASYARAKAT PANTAI MELALUI PENERAPAN JAMBAN KELUARGA DARI KAYU MODEL PANGGUNG YANG AMAN TERHADAP AIR PASANG - M., Mustamin; Taqwin, Muh.; Rahmat, Heri; Z., Zainuddin (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
The purpose of this is PKMM communities living in coastal areas in Palanro Barru to: (1) recognize that the family latrine construction secure against the tide, (2) to design, create the framework, floors, walls and roof of wooden models of family latrines and septic stage -tanks of masonry healthy and safe against the tide. The target audience of this program is people who live in coastal areas in Palanro, District Mallusetasi Barru. The method used in the delivery of education materials is a lecture, discussion and question and answer, demonstration method is used for training. The results obtained are: (1) Know the family latrine construction secure against the tide, (2) skilled designing, making framework, floors, walls and roof of wooden models of family latrines and septic-tanks stage of masonry healthy and safe against the tide.